Transition Metal Oxodiperoxo Complex Modified Metal-Organic Frameworks as Catalysts for the Selective Oxidation of Cyclohexane - Hong, Yuechao (Materials (Basel), 2020)
In this work, a series of modified metal-organic frameworks (MOFs) have been prepared by pre- and post-treatment with transition metal oxodiperoxo complexes (MoO(O(2))(2), WO(O(2))(2), and KVO(O(2))(2)). The obtained materials are characterized by XRD, FTIR, SEM, TEM, inductively coupled plasma atomic emission spectrometry (ICP-AES), and X-ray photoelectron spectroscopy (XPS), as well as by N(2) adsorption/desorption measurement. The characterization results show that transition metal oxodiperoxo complexes are uniformly incorporated into the MOF materials without changing the basic structures. The performance of cyclohexane oxidation on metal oxodiperoxo complex modified MOFs are evaluated. UiO-67-KVO(O(2))(2) shows the best performance for cyclohexane oxidation, with 78% selectivity to KA oil (KA oil refers to a cyclohexanol and cyclohexanone mixture) at 9.4% conversion. The KA selectivity is found to depend on reaction time, while hot-filtration experiments indicates that the catalytic process is heterogeneous with no leaching of metal species.